Effect of cutting tool tip position on real cutting tool deflection in turning - Kiyak, Murat (EMERALD GROUP PUBLISHING LTD, 2020)
In the turning process, the surface quality depends on factors such as the tangential cutting force, depth of cut, tool overhang and cutting tool geometry. In the literature, most of these factors and their effects on the turning process have been investigated. However, the cutting tool deflection has not been investigated in detail. In addition, it is known that the prediction of the cutting tool tip displacement is an important and leading factor to obtain the desired surface quality and cylindricity. It is assumed that the cutting tool is generally a cantilever beam and the tangential force is applied on its shank axis. This condition is not always valid for all turning operations and toolholders due to the fact that the cutting tool tip is not always on the shank axis. In this study, the torsion effect on the cutting tool was investigated in addition to tool deflection. The real deflections of the different toolholders were calculated separately by conducting a new theoretical approach. The effectiveness of the new approach was verified by using the finite-element method (FEM). Depending on the results, the tool deflections calculated by using the new analytical method were quite compatible with FEM and experiments.
Keywords: manufacturing; mechanical properties; surface roughness; SURFACE-ROUGHNESS PREDICTION; STABILITY; PARAMETERS; WEAR; OVERHANG; QUALITY; FINISH; STATES; MODEL; Materials Science